PENDEKATAN MULTIKULTURAL YANG BERLANDASKAN KONSTRUKTIVISME SEBAGAI UPAYA PENINGKATAN PEMAHAMAN KONSEP DALAM PEMBELAJARAN MATEMATIKA BERMAKNA PADA PENDIDIKAN NONFORMAL - Ade Kusmiadi; Euis Eti Rohaeti; Heris Hendriana (Jurnal Ilmiah Visi, 2009)
Leaning is expected to be the process of cultural transformation and an attempt to manage the environments which give nuance for students to grow and develop with optimum. Multicultural approach is designed by focusing on the importance of social pluralism, multicultural, ethnics and contextualizing. In multicultural approach, the process of education is centered on students or certain community in which the teachers understand beliefs and values of socio cultural students in the context of society culture in designing learning model. In order to introduce a new mathemtics concept to the students, teachers have to relate the concepts known by students before. By using the contexts related to culture known by the students, it will make students feel that knowledge has been part of them and students will not feel it as something new, so that students will feel their learning meaningful. Based on constructivism view, if students feel that knowledge has been part of them and learning is meaningful, students will be motivated to find their own way to keep and get deeper on knowledge in their study. Their attempt to find their own way itself is the main point of constructivism learning. Thus, by using this approach it is expected there will be a new belief system in a theory and concept based on the culture known by students, so that that culture can be applied and kept continually through the way of thinking, ttpoint of view and ways of doing something had by young generation. The result of the study reveals that understanding toward mathematics concept of students using multicultural appraoch is better than those using common appraoch.